Are you ready? Data analytics is reshaping the work of accountants - GOH, Clarence (Institutional Knowledge at Singapore Management University, 2017)
According to the 2016 State of Analytics and Data Science reportpublished by data analytics firm Mu Sigma, 65% of senior business leaderssurveyed in the United States believe that data analytics has influenced theirbusiness in a positive way.